Artificial Intelligence in Democracy: Unraveling the Influence of Social Bots in Brexit through Cybernetics - Chen, Shuqi (Transactions on Social Science, Education and Humanities Research, 2024)
This paper delves into the implications of AI on the democratic process, particularly concerning the manipulation of information flows via cybernetic mechanisms. Through the lens of cybernetics, AI orchestrates information dissemination on web platforms, notably through Social Bots, autonomous programs simulating human behavior to sway public discourse. This study examines how AI's manipulation of information, exemplified by the case of Social Bots in the 2016 UK Brexit referendum, influences democratic participation and election outcomes. Amidst a regulatory landscape characterized by lax oversight, understanding the intricate interplay between AI, cybernetics, and democratic processes is imperative for addressing ethical concerns and safeguarding democratic integrity. This paper underscores the urgency of establishing industry benchmarks to regulate AI's role in shaping public discourse and its consequential impact on democratic decision-making.